Assessment of Vegetative, Floral and Corm Characteristics in Gladiolus Genotype at Malepatan, Pokhara, Nepal - Devkota, Urmila; Adhikari, Prakriti; Lohani, Santosh; Sharma, Shreya (Nepalese Horticulture, 2023)
Gladiolus (Gladiolus grandifloras L.), recognized for its bright, distinctively textured blossoms, is first commercially grown cut flower in Nepal. A study was carried out to assess vegetative, floral, and corm characteristics in gladiolus genotypes in Maltepatan, Pokhara. Twelve genotypes namely NGRV0130 (ARSDG-04), RARSLG-014-1.1, RARSLG-014-1.11, RARSLG-014-2.8, RARSLG-014-3.10(A), RARSLG-014-3.11, RARSLG-014-6.8, RARSLG-014-6.12, RARSLG-014-6.13, RARSLG-014-7.27(A), RARSLG-014-8.22, RARSLG-014-9.10 were evaluated from March 02-August 07, 2022. The experiment was laid out in a Randomized complete block design with three replications. The crop geometry was maintained at 50 cm × 28.5 cm in a four-meter square plot containing twenty-eight corms per plot. The genotype RARSLG-014-3.11 was found earliest on days to 50% sprouting, spike initiation, and floret opening. The genotype RARSLG-014-6.12 was noted to have maximum number of florets per spike and number of spikes per hill, longest rachis length, and a maximum number of cormels. Similarly, the genotype RARSLG-014-1.11 was a promising genotype in having a maximum number of corms. The longest length of the spike (140.66 cm) was found for genotype RARSLG-014-6.8.